A Behavioral Science Approach to Personnel Selection - Dillman, Everett G. (Academy of Management Journal, 1967)
Although traditional methods of selection of personnel have accomplished a great deal in predicting job performance, the perspective of these methods is too narrow. In this article a behavioral model is developed which can be used to examine the probable effects of the organition on the applicant, and the reciprocal effects of the applicant on the organization.